PENENTUAN KOORDINAT GLOBAL POSITIONING SYSTEM (GPS) RAMBU DILARANG PARKIR UNTUK MEREKAM PELANGGARAN BERBASIS INTERNET OF THINK (IOT) - Alfriyani, Ega Pratama; Winardi, Slamet (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
The Industrial revolution 4.0 in the field of technology that is Internet of think (IoT) then to overcome the problem of traffic signs violations, need for a tool that can help police to monitor users the way through the internet with Android applications. And in 2018 Rizal makes an application of digital STNK based on Internet of think (IoT) which uses Wemos D1 mini as a microcontroller. Lack of this tool is the absence of violation record features and Global positioning system (GPS). The purpose of this study is to create a tool that can record violations of parking sign and to geting latitude and longtitude coordinates using the GPS function on the cellphone. To obtain data in the form of a police number, date, and time, the following devices are used: wemos d1 mini as a server, wemos d1 mini as a client, codular creator to create android applications.